Modulating N doping in cobalt-derived catalyst from zeolitic imidazolate frameworks for high performance zinc-air batteries - Ramírez-Díaz, Adrián; Béjar, José; Delgado, Anabel D.; Suarez-Barajas, Alexander; Guerra-Balcázar, Minerva; Arjona, Noé; Álvarez-Contreras, Lorena (Materials letters, 2024)
[Display omitted] •Nitrogen dopants significantly modify ZIF-derived carbon structures and performance.•CM-ZIF balanced nitrogen species boost Zn-air battery performance.•CM-ZIF presented an onset potential of 0.9 V vs. NHE for the ORR.•In the ZAB, an open circuit voltage of 1.53 V (120 mV below the theoretical) was found.•The round-trip efficiency was 68.8% for the ZAB assembled with CM-ZIF. In this work, the N-content was varied using ammonium hydroxide (A), urea (U), and melamine (M) impregnated in a zeolitic imidazolate framework (ZIF-67) with a Co to Zn ratio of 7:93. The N-doped ZIF-derived carbon materials and the reference ZIF Co 7:93 underwent pyrolysis under identical conditions, yielding C-ZIF, CA-ZIF, CU-ZIF, and CM-ZIF. Different nitrogen sources mainly affected the surface area and graphitic-N content, yielding up to three times the N-content of the reference. All materials presented ORR onset potentials near 0.9 V and E10mA cm−2 near 1.6 V for the OER. However, CM-ZIF enabled rechargeability at different current densities, with a round-trip efficiency of 68.8 % at 5 mA cm−2, decreasing only to 54 % at 15 mA cm−2.